Efecto antimicótico de la asociación de cinnamomum zeylanicum y fluconazol sobre candida albicans - Vaca Bautista, Bill Jhonson Maguin (2017)
To evaluate the effect of the association between cinnamon’s essential oil (Cinnamomum zeylanicum) and fluconazole on Candida albicans. MATERIAL AND METHOD: The steam distillation method was used to obtain the essential oil of Cinnamomun zeylanicum. The antifungal effect of the association with fluconazole on Candida albicans was determined by the disc diffusion method, using concentrations of 25, 50, 75% and 100% of essential oil, in addition to the control drug (fluconazole). RESULTS: All the concentrations of the essential oil had an antimycotic effect, because the inhibition halos were greater than 8 mm according to Duraffourd scale; in addition, to a higher concentration used in association with fluconazole, a greater antimycotic effect, which is a synergistic effect of power. In the analysis of variance (ANOVA), a value of p = 0.000 (p <0.005) was obtained for the antimycotic effect on Candida albicans of the essential oil of Cinnamomum zeylanycum, as well as in its association with fluconazole, which indicates that there is highly significant difference between all the groups CONCLUSION: The association of essential oil of Cinnamomum zeylanicum with fluconazole on Candida albicans has a synergistic effect of potency